The theses for degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
Ye.V. Komarova – Chronic constipation at children: medical and social issues (The theses for PhD degree).A.A. Repin – Characteristic of lipid metabolism disorders and treatment options at the latent form of celiac sprue (The theses for MD degree).I.D. Uspenskaya – Clinical and pathogenic role of the body defense system disorders at diseases with malabsorbtion syndrome in children (The theses for PhD degree).Ye.V. Motuzova – Comparative evaluation of clinical and pharmacoeconomical efficacy of treatment of non erosive reflux disease by proton pump inhibitors (The theses for MD degree).